ANALYSIS OF RISK FACTORS IN THE INCIDENT OF RESPIRATORY TRACT INFECTIONS IN BABIES AND BREAST MILK EXCLUSIVELY AT RSIA PURI GARCIA SERANG - Sihaloho, Juliana Sinurlitani; Fauzi, Achmad (HEARTY, 2025)
Background:Based on WHO (2022), it is revealed that the mortality rate for ARI in children under five is the cause with the highest prevalence. The high incidence of effects on the respiratory tract in Indonesia, especially in Serang, means that it is necessary to carry out an analysis regarding the factors that cause respiratory tract infections, especially in toddlers. Research Objectives:To determine the relationship between factors that influence the incidence of respiratory tract infections in babies with exclusive breastfeeding at RSIA Puri Garcia Serang Research Methods: descriptive research method with a quantitative approach, the design used is the Cross-Sectional method. The population in this study was all 36 babies aged 0-6 months at RSIA Puri Garcia Serang. The sampling technique in this research used a total sampling technique. Data collection techniques in this research are interviews and questionnaires. The data collection technique was carried out using anthropometric measurements with the aim of knowing the nutritional status of each respondent. Research Results:Shows that there is a significant relationship between a history of exclusive breastfeeding and the incidence of infant respiratory tract infections at RSIA Puri Garcia Serang with ap value of 0.001.